Identification of Asbestos Content in Bulk Materials Imported in Nepal - Pathak, Arvind; Giri, Manbir; Pokhrel, Bishnu; Wagle, Manoj Nidhi (Scientific World, 2020)
The bulk materials include the construction materials such as plaster sand gravel and cement as well as raw materials. Asbestos is the naturally occurring magnesium silicate mineral fibers which has high tensile strength, flexibility and resistance to chemicals, high temperature and stress; this is why it has been considered and used in bulk materials. These mineral fibers are needle shaped and can stick to lung tissue when inhaled and cause inflammation and serious health problems such as asbestosis, mesothelioma and lung cancer or internal fibrosis. It can be detected by simple microscopic method using mineral acid and heat treatment. The method would help in quality analysis of asbestos fiber and save from asbestos induced disease and to develop alternative materials of asbestos fiber material.